2014
DOI: 10.1177/0886260514555006
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying

Abstract: Although the research on cyberbullying has increased dramatically in recent years, still little is known about how cyberbullying participant groups (i.e., cyberbullies, cybervictims, and cyberbully-victims) differ from one another. This study aims to discriminate between these groups at an individual and relational level by controlling for age and gender. Self-control, offline aggression, and self-esteem are analyzed as individual-level variables. Parental attachment and peer rejection are involved as relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 86 publications
(183 reference statements)
3
34
0
3
Order By: Relevance
“…Low communication with parents is a risk factor for cyber victimization.Özdemir (2014) found a positive association between cyber victimization and less communication with parents by surveying 337 Turkish students aged 15-18 years. Also parental attachment was found to be a risk factor for cyber victimization, as reported byBayraktar et al (2014). The study found that cyber victimization is associated with poor parental attachment.…”
mentioning
confidence: 50%
See 4 more Smart Citations
“…Low communication with parents is a risk factor for cyber victimization.Özdemir (2014) found a positive association between cyber victimization and less communication with parents by surveying 337 Turkish students aged 15-18 years. Also parental attachment was found to be a risk factor for cyber victimization, as reported byBayraktar et al (2014). The study found that cyber victimization is associated with poor parental attachment.…”
mentioning
confidence: 50%
“…Who the children hang around with and the lack of prosocial peer influences were found predictors in the Canadian longitudinal study of Cappadocia, Craig, & Pepler (2013) of future cyberbullying involvement. This is true also for peer rejection, with cyberbullies more likely to be rejected than noncyberbullies (Bayraktar et al 2014;Wright & Li, 2013) and experiencing greater social isolation as well as lack of perceived peer support, found in the systematic review (Kowalski et al, 2014), and specifically also in the Spanish (Calvete et al, 2010) and US (Williams & Guerra, 2007) studies. Clearly peer factors can be considered dynamic risk factors that can change in time or with tailored intervention.…”
Section: Accepted Manuscriptmentioning
confidence: 70%
See 3 more Smart Citations